Testing and Numerical Studies on Transverse Responses of Cable-stayed Bridge Full Model under Transverse Non-uniform Excitations. Issue 6 (26th April 2022) - Xie, Wen; Sun, Limin; Lou, Menglin
ABSTRACT: A cable-stayed bridge full model was tested to study the travelling wave effects on the transverse acceleration frequency spectra, seismic responses, and pile-soil interactions under transverse non-uniform excitations. The results indicate that the non-uniform excitations affect the transverse acceleration frequency spectra of the girder. The non-uniform excitations increase the displacement at 3/4-span of the girder but decrease the displacements at 1/2- and 1/4-span of the girder. The pile-soil interaction effects of one tower increase, whereas those of another tower decrease due to the non-uniform excitations. The numerical model could generally capture the seismic response changes caused by the non-uniform excitations.